Grid Computing Achievements and Prospects - Gorlatch, Sergei; Fragopoulou, Paraskevi; Priol, Thierry (Springer US : Imprint: Springer, 2008)
Grid Computing: Achievements and Prospects, the 9th edited volume of the CoreGRID series, includes selected papers from the CoreGRID Integration Workshop, held April 2008 in Heraklion-Crete, Greece. This event brings together representatives of the academic and industrial communities performing Grid research in Europe. The workshop was organized in the context of the CoreGRID Network of Excellence in order to provide a forum for the presentation and exchange of views on the latest developments in grid technology research. Grid Computing: Achievements and Prospects is designed for a professional audience, composed of researchers and practitioners in industry. This volume is also suitable for graduate-level students in computer science.